EFSUMB Guidelines on Interventional Ultrasound (INVUS), Part IV – EUS-guided interventions: General Aspects and EUS-guided Sampling (Short Version) - Jenssen, C.; Hocke, M.; Fusaroli, P.; Gilja, O. H.; Buscarini, E.; Havre, R. F.; Ignee, A.; Saftoiu, A.; Vilmann, P.; Burmester, E.; Nolsøe, C. P.; Nürnberg, D.; D’Onofrio, M.; Lorentzen, T.; Piscaglia, F.; Sidhu, P. S.; Dietrich, C. F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
The fourth part of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) Guidelines on Interventional Ultrasound describes general aspects of endoscopic ultrasound-guided diagnostic and therapeutic interventions and assesses the evidence for endoscopic ultrasound-guided sampling. Endoscopic ultrasound combines the most advanced high-resolution ultrasound imaging of lesions within the wall and in the vicinity of the gastrointestinal tract and safe and effective fine needle-based tissue acquisition from these lesions. The guideline addresses the indications, contraindications, techniques, adverse events, training and clinical impact of EUS-guided sampling. Advantages and drawbacks are weighed in comparison with image-guided percutaneous biopsy. Based on the most current evidence, clinical practice recommendations are given for crucial preconditions and steps of EUS-guided sampling as well as for safe performance. Additionally, the guideline deals with the principles and reliability of cytopathological reporting in endoscopic ultrasound-guided sampling (short version; the long version is published online).
Keywords: guideline; endoscopic ultrasound; EUS-guided sampling; EUS-guided fine-needle aspiration; rapid onsite cytopathological evaluation; cytopathological reporting; quality indicators; adverse events